PENGARUH PEMBERIAN EKSTRAK KERING DAUN SUKUN (ARTOCARPUS ALTILIS) TERHADAP KADAR GLUKOSA DARAH PADA TIKUS PUTIH DIABETES MELITUS - Darma Putra, Gusti Bagus Jelantik (Coping: Community of Publishing in Nursing; Vol 2 No 3 (2014): JURNAL EDISI SEPTEMBER-DESEMBER 2014, 2014)
Breadfruit leaf is a natural material (herb) which can be used as an anti-hyperglycemic drug. One of the compounds in breadfruit leaf that can decrease blood glucose level is Quercetin. A variety of polar solvents can be used to activate this compound in breadfruit leaf, such as  water, ethanol and methanol. The use of ethanol, even more selective and have positive role when separating flavonoid in breadfruit leaf, but ethanol extract in liquid or viscous form also has some weaknesses, wherein the extract can not be stored for a long time and easily damaged because of water medium in the extract is an ideal and great place for fungus to multiply. Based on these facts, it is necessary to create a new method in processing breadfruit leaf extract to obtain better results than the previous, by using dry extract. This study aims to determine the effect of dry extract of breadfruit leaf (Artocarpus altilis) on blood glucose level in mice with diabetes mellitus. This research is a true experimental with a completely randomized design. The treatment group is administration of breadfruit leaf dry extract at a dose of 135 mg, 270 mg, 405 mg and 1 negative control group which have no intervention. Normality test using Shapiro-Wilk and data was analyzed with One Way Anova test and show significant differences (p: 0.000 <? 0:05). The results of analysis with post hoc tests show significant differences between treatment groups dose 1 with dose 2 (p <0.05). The conclusions of this study are breadfruit leaf dry extract have some effects on blood glucose level of mice with diabetes mellitus, and there are significant differences in blood glucose levels between treatment groups which have given breadfruit leaf dry extract dose 2 with dose 3.
Keywords: Breadfruit Leaf Dry Extract, Blood Glucose, Diabetes Mellitus, White Male Rats